PD173074, a selective FGFR inhibitor, reverses MRP7 (ABCC10)-mediated MDR - Nagaraju Anreddy; Atish Patel; Kamlesh Sodani; Rishil J. Kathawala; Eugenie P. Chen; John N.D. Wurpel; Zhe-Sheng Chen (Elsevier, 2014)
Multidrug resistance protein 7 (MRP7, ABCC10) is a recently identified member of the ATP-binding cassette (ABC) transporter family, which adequately confers resistance to a diverse group of antineoplastic agents, including taxanes, vinca alkaloids and nucleoside analogs among others. Clinical studies indicate an increased MRP7 expression in non-small cell lung carcinomas (NSCLC) compared to a normal healthy lung tissue. Recent studies revealed increased paclitaxel sensitivity in the Mrp7−/− mouse model compared to their wild-type counterparts. This demonstrates that MRP7 is a key contributor in developing drug resistance. Recently our group reported that PD173074, a specific fibroblast growth factor receptor (FGFR) inhibitor, could significantly reverse P-glycoprotein-mediated MDR. However, whether PD173074 can interact with and inhibit other MRP members is unknown. In the present study, we investigated the ability of PD173074 to reverse MRP7-mediated MDR. We found that PD173074, at non-toxic concentration, could significantly increase the cellular sensitivity to MRP7 substrates. Mechanistic studies indicated that PD173074 (1 μmol/L) significantly increased the intracellular accumulation and in-turn decreased the efflux of paclitaxel by inhibiting the transport activity without altering expression levels of the MRP7 protein, thereby representing a promising therapeutic agent in the clinical treatment of chemoresistant cancer patients.